2011
DOI: 10.1186/1748-717x-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic agents in the treatment of recurrent or newly diagnosed glioblastoma: Analysis of single-agent and combined modality approaches

Abstract: Surgical resection followed by radiotherapy and temozolomide in newly diagnosed glioblastoma can prolong survival, but it is not curative. For patients with disease progression after frontline therapy, there is no standard of care, although further surgery, chemotherapy, and radiotherapy may be used. Antiangiogenic therapies may be appropriate for treating glioblastomas because angiogenesis is critical to tumor growth. In a large, noncomparative phase II trial, bevacizumab was evaluated alone and with irinotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 97 publications
0
80
1
1
Order By: Relevance
“…The clinical significance of this phenomenon remains to be determined. Several studies of patients with glioblastoma concluded that the proportion of distant recurrences does not differ between patients receiving bevacizumab and those receiving other regimens [Beal et al 2011;Chamberlain, 2011;Platten et al 2010;Pope et al 2011;Shapiro et al 2009]. Given that different tumor types may respond differently to antiangiogenic therapies, the question of whether antiangiogenic therapies select for a more aggressive malignant phenotype remains an area of active discussion and investigation.…”
Section: Disease Progression: Definitions and Managementmentioning
confidence: 99%
“…The clinical significance of this phenomenon remains to be determined. Several studies of patients with glioblastoma concluded that the proportion of distant recurrences does not differ between patients receiving bevacizumab and those receiving other regimens [Beal et al 2011;Chamberlain, 2011;Platten et al 2010;Pope et al 2011;Shapiro et al 2009]. Given that different tumor types may respond differently to antiangiogenic therapies, the question of whether antiangiogenic therapies select for a more aggressive malignant phenotype remains an area of active discussion and investigation.…”
Section: Disease Progression: Definitions and Managementmentioning
confidence: 99%
“…Excessive microvascular proliferation and VEGF overexpression were identified in tumor tissues from patients with GBM. Higher intra-tumoral as well as plasma VEGF concentrations were associated with rapid disease progression and presence of early recurrence of GBM (72)(73)(74)(75)(76)(77). Therefore, the evaluation of antiangiogenic and anti-VEGF agents in GBM is highly needed.…”
Section: Inhibition Of Angiogenesis In Gbmmentioning
confidence: 99%
“…Although lack of standardized imaging criteria to define relapse makes these findings controversial, an invasive response likely takes place after blood vessel inhibition (reviewed in ref. 51). Increasing experimental evidence points to MET as a major culprit.…”
Section: Met Inhibitors Radiotherapy and Antiangiogenesismentioning
confidence: 99%